Pengaruh Karakteristik Keuangan Terhadap Konservatisme Akuntansi - Windi Amaliana; Rita Wijayanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study analyzes the effect of financial characteristics, such as Growth Opportunity, Return on Equity, Sales Growth, Return on Assets, Capital Intensity, Investment Opportunity Set, Financial Distress, Financial Leverage, Global Diversification, and Uncertainty Environment on accounting conservatism. The population in this study were 64 LQ45 companies listed on Indonesia Stock Exchange in 2020-2023. The sampling technique used purposive sampling, with 25 companies that met the criteria. The data used are secondary data obtained from the company's annual report. Data analysis was conducted using multiple linear regression analysis with the SPSS program. The results show that Growth Opportunity and Return on Equity have an effect on accounting conservatism. Meanwhile, Sales Growth, Return on Assets, Capital Intensity, Investment Opportunity Set, Financial Distress, Financial Leverage, Global Diversification, and Uncertainty Environment do not have an effect on accounting conservatism.